Pharmaceutical industry practices on genotoxic impurities - Lee, Heewon (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'A great deal of confusion and uncertainty over genotoxic impurity (GTI) identification, assessment, and control exists in the pharmaceutical industry today. Pharmaceutical Industry Practices on Genotoxic Impurities strives to facilitate scientific and systematic consensus on GTI management by presenting rationales, strategies, methods, interpretations, practices, and case studies from the pharmaceutical industry. Featuring the contributions of industry leaders from nine major pharmaceutical companies, this authoritative text:Explores the safety, quality, and regulatory aspects of GTIsProvides an overview of the latest FDA and EMEA guidelinesExplains the how and why of various GTI control tactics and practicesDescribes genotoxicity evaluation, acceptable exposure calculation, and analytical methods for testingIncludes real-life examples of GTI control in drug substance and drug product development processesContaining case studies from large and small pharmaceutical firms in multiple geographical regions, Pharmaceutical Industry Practices on Genotoxic Impurities supplies an overview of and a current framework for GTI control in the pharmaceutical industry, demonstrating how proper management of GTIs can occur with the appropriate guidance, a firm grasp of the practical implications, and effective information sharing between disciplines'--
'Preface According to the World Health Organization's International Agency for Research on Cancer (IARC) (Technical Publication No. 24, 1994), genotoxicity is defined as structural changes at the level of a gene. It is also defined as a broad term that refers to any deleterious change in the genetic material regardless of the mechanism by which the change is induced, as stated by ICH S2(R1),'Guidance on Genotoxicity Testing and Data Interpretation for Pharmaceuticals Intended for Human Use.' Genotoxic compounds have the theoretical potential to damage DNA at any level of exposure, leading to tumor development. This makes the toxicological assessment and determination of acceptable limits of genotoxic impurities (GTIs) difficult. GTIs have become an intensely debated topic in the pharmaceutical industry in recent years. My experiences in the internal and external discussions in meetings and conferences indicate that there is a great deal of confusion and uncertainty over identification, assessment, and control of GTIs. GTIs require different rationale and strategies from'regular' or'ordinary' impurities. Proper management of GTIs entails appropriate guidance and strategies, effective communication between various disciplines, sharing information and results, and understanding of the overall implications. The goal of this book is to present the rationale, strategies, methods, interpretation, practices, and case studies in the pharmaceutical industry in order to facilitate scientific and systematic consensus establishment on GTIs'--
Includes bibliographical references and index.
Keywords: MEDICAL / Pharmacology; SCIENCE / Chemistry / Analytic; SCIENCE / Research & Methodology; Mutagenicity Tests -- methods; Mutagens -- adverse effects; Mutagens -- toxicity; Toxicologie g{u296E}ique.; Micaments -- Toxicologie; Mutag{u196E}es.; Mutagenicity Tests -- methods; Mutagens -- adverse effects; Mutagens -- toxicity; Drugs -- Toxicology; Genetic toxicology